2012
DOI: 10.1007/s00018-012-0977-6
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 regulates neuronal apoptosis by adjusting ApoER2 levels and signaling

Abstract: The secreted protease proprotein convertase subtilisin/kexin type 9 (PCSK9) binds to low-density lipid (LDL) receptor family members LDLR, very low density lipoprotein receptor (VLDLR) and apolipoprotein receptor 2 (ApoER2), and promotes their degradation in intracellular acidic compartments. In the liver, LDLR is a major controller of blood LDL levels, whereas VLDLR and ApoER2 in the brain mediate Reelin signaling, a critical pathway for proper development of the nervous system. Expression level of PCSK9 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 55 publications
3
92
1
Order By: Relevance
“…For example, in contrast to the LDLR, the GOF D374Y PCSK9 does not degrade these other receptors more efficiently than wild-type PCSK9. 42 The receptors LDLR, VLDLR, and ApoER2 have been confirmed as PCSK9 target proteins in mice 25,26,65,66 and the LDLR in monkeys 67 and human. 68 Recently, we showed that PCSK9 can enhance the degradation of LRP1 in various cells 44 although proof of this activity in vivo is still lacking.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 96%
“…For example, in contrast to the LDLR, the GOF D374Y PCSK9 does not degrade these other receptors more efficiently than wild-type PCSK9. 42 The receptors LDLR, VLDLR, and ApoER2 have been confirmed as PCSK9 target proteins in mice 25,26,65,66 and the LDLR in monkeys 67 and human. 68 Recently, we showed that PCSK9 can enhance the degradation of LRP1 in various cells 44 although proof of this activity in vivo is still lacking.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 96%
“…Like other members of the LDL-R family, VLDL-R and apoE receptor 2 undergo lysosomal degradation after binding of PCSK9 to the EGF-A domains of the receptors. 60,61 Notably, PCSK9 has been implicated in central nervous system development 62 and, as noted above, was shown to enhance neuronal apoptosis, 19,63 an effect mediated by degradation of the apoE receptor 2. 63 Conversely, inhibition of PCSK9 led to an increase in cell viability for up to 24 hours in the setting of neural apoptosis induced by potassium deprivation.…”
Section: Brainmentioning
confidence: 90%
“…60,61 Notably, PCSK9 has been implicated in central nervous system development 62 and, as noted above, was shown to enhance neuronal apoptosis, 19,63 an effect mediated by degradation of the apoE receptor 2. 63 Conversely, inhibition of PCSK9 led to an increase in cell viability for up to 24 hours in the setting of neural apoptosis induced by potassium deprivation. 63 There is conflicting evidence bearing on the possibility of a relationship of brain PCSK9 expression to the pathophysiology of Alzheimer disease.…”
Section: Brainmentioning
confidence: 90%
“…In a recent animal study, the authors observed a proapoptotic effect in cerebellar neurons of PCSK9 (mediated by apoE receptor 2 degradation) that was independent of N-methyl-D-aspartate receptor function. 29 Some studies suggested involvement of this convertase in the development of Alzheimer's disease, 30,31 in that it is able to generate amyloid β-peptide. 32 Controversial findings came from other research.…”
mentioning
confidence: 99%